Model of Good Governance Principles in Improving the Performance and Quality of Services of Regency/City Population and Civil Registration Services in West Sumatera - Mulia, Rizki Afri; Putri, Rianda Prima; Ananda, Bobi Rizki; Saputra, Nika; Syamsir, Syamsir (Faculty of Social Science, Universitas Negeri Padang, 2023)
Good Governance is the principle that can improve the performance and quality of services at the District/City Population and Civil Registration Service (Disdukcapil) in West Sumatra. This research aims to analyze a model of Good Governance principles that can improve the performance and quality of services for the District/City Disdukcapil in West Sumatra. The principles of Good Governance used in this research consist of accountability, participation, efficiency and effectiveness, transparency, rule of law, and responsiveness. This research uses quantitative methods with Structural Equation Model data analysis techniques. The research sample consisted of 118 respondents who were employees of the Regency/City Disdukcapil in West Sumatra. The findings of the study indicate that implementing the Good Governance principles model can potentially enhance the performance and service quality of the District/City Disdukcapil in West Sumatra. This improvement is attributed to the adherence to key concepts such as accountability, transparency, rule of law, and responsiveness. Simultaneously, the concepts of efficiency, effectiveness, and participation do not substantially influence the performance and service quality of the District/City Disdukcapil in West Sumatera.